Serum creatine kinase and other profile of duchenne muscular dystrophy and becker muscular dystrophy: A cross-sectional survey in a tertiary care institution at Kolkata - Santa Saha; Anindita Joardar; Sarnava Roy; Tanushree Mondal; Gautam Gangopadhyay; Dibakar Haldar; Harendra Nath Das (CHRISMED Journal of Health and Research, 2021)
Background: Serum creatine kinase (CK) level is increased muscular dystrophy (MD) and may be used as a clue to identify MDs. Objective: The objective is to compare CK levels between Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD), to correlate value of serum CK with number of deletions, duration of illness and to establish a cut off value of CK for screening. Materials and Methods: A cross-sectional survey was carried out in a tertiary care institute of Kolkata. Clinically diagnosed patients of 139 DMDs and 50 BMDs along with 69 age-matched individuals suffering from diseases other than MDs was included. Estimation of serum CK levels and gene analysis were done for all. Results: DMD victims were found to be younger with low age of onset and lesser disease duration but higher serum CK level compared to those having BMD. Most of the genetic deletions were happened in distal region of dystrophin gene and a significant difference was revealed to exist between DMD and BMD neither in regard to proportion of overall deletion nor deletions in proximal and distal region. However, gene deletion was found absent in 31% and 42% of DMD and BMD cases. Serum CK level of 511.5 unit/L was seemed to be a reliable cut-off for detection of DMD and BMD with 97.3% sensitivity, 100% specificity, and area under the curve 0.989 with a P = 0.000. Conclusion: In case of nonavailability of genetic test facility as well as negative genetic test serum CK may be tried for identifying MD.